Amérique Sepentrionale. - Giraldon (1800)
Map shows North America from Russian America [Alaska] to Greenland to Mexico and Central America; West Indies, major cities; Florida panhandle extending to Louisiana, United States extending only to the Mississippi River; areas of Native American habitation. Relief shown pictorially and by hachures. Scale not given.